Protection et restauration de la plaine inondable du Danube (Roumanie) : de l’état des lieux au cas du lac Suhaia - Gabriela Ioana-Toroimac (Développement Durable et Territoires)
Romania’s concerns for the protection and restoration of Danube floodplain started in 1990 and intensified during the 2000s. Based on this favorable framework, approximately new fifty protected areas were created ; one of them is Suhaia Special Protection Area (Natura 2000), around Suhaia Lake, declared in 2007. It protects the status of the floodplain as modified by human interventions since the 1960s (i.e. river and lake diking for flood protection, agricultural activities). The GIS analysis shows layers overlapping – protected area, dykes, agricultural lands – thus a conflict between these activities with contradictory goals.